Improve the Performance of Wireless Sensor Network Used to Monitor Containers on the Ships - جمال خليفة; مريم بركات (Latakia University Journal -Engineering Sciences Series, 2022)
The Wireless Sensor Network (WSN) uses a large number of sensor nodes that spread in a specific place and work with each other to monitor a studied phenomenon to obtain specific information and pass it to specific location. The research presents an improved model of a hybrid wireless sensor network containing two types of Zigbee and WIFI transmission protocols that monitors commercial containers on the deck of ships. The research presents a solution to the problem of data loss in the hybrid wireless transmission by using software solutions to design a gateway capable of translating between the two different types of protocols Zigbee & WIFI with achieving optimum performance for the work of this gate. The aforementioned wireless sensor network will be modeled in several scenarios using the NS3 program, based on the simulation results, it was found that software-designed gateway has improved the hybrid system in terms of time delay and the rate of receiving transmitted packages compared to previous studies.